Reservoir analysis of the compartmentalized Mississippian ages Spivey-Grabs field, south central Kansas - Stevens, Logan (Kansas State University, 2016)
Mississippian chert reservoirs, also known as chat reservoirs among the mid-continent in Kansas and northern Oklahoma, produce an abundant amount of hydrocarbons. Since the 1920s, chat reservoirs in Kansas have yielded over 380 million bbl of oil and 2.3 tcf of natural gas. The largest Mississippian field in south-central Kansas is the Spivey-Grabs, which spans Kingman and Harper Counties. Development of the Spivey-Grabs Mississippian reservoir, and continued production within the field, has been compromised by compartmentalization within the field, resulting in unpredictable producing rates. Previous research has investigated the differences of the fluids within the separate compartments (Evans, 2011; Kwasny, 2015), and identified the existence of at least two oil types of differing viscosity (Kwasny, 2015). The objective of this research was to determine whether the compartmentalization of the reservoir is controlled by the different lithologic characteristics between the various compartments. This was accomplished by examining drill cuttings under binocular microscope, under a petrographic microscope using digital imaging software, and under the high magnification of a scanning electron microscope. Calculated rock porosity from ImageJ software showed variation among the wells selected for this study; but the porosity variation does not correlate with differences in fluid viscosity that was previously observed, i.e. heavy and light viscosity oils (Kwasny, 2015). Heavy oils were seen in wells that had both higher and lower porosity values, and the same is true for the distribution of light oils. This suggested that fluid viscosity is the major controlling factor in compartmentalization in the Spivey-Grabs and not rock properties.
Keywords: Compartmenalization; Reservoir; Mississippian chert; Petroleum; Spivey-Grabs; Petroleum Geology (0583)